2021
DOI: 10.1002/ptr.6991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phytochemicals on macrophage cholesterol efflux capacity: Impact on atherosclerosis

Abstract: High‐density lipoprotein cholesterol (HDL) is the major promoter of reverse cholesterol transport and efflux of excess cellular cholesterol. The functions of HDL, such as cholesterol efflux, are associated with cardiovascular disease rather than HDL levels. We have reviewed the evidence base on the major classes of phytochemicals, including polyphenols, alkaloids, carotenoids, phytosterols, and fatty acids, and their effects on macrophage cholesterol efflux and its major pathways. Phytochemicals show the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 198 publications
0
25
0
Order By: Relevance
“…Therefore, stabilizing the mitochondria can prevent doxorubicin-induced cardiotoxicity ( Montaigne et al, 2010 ). Indeed, recent studies have reported that natural products may be appropriate alternatives for chemical agents in various diseases ( Momtazi et al, 2017 ; Bagherniya et al, 2018 ; Alidadi et al, 2020 ; Soltani et al, 2021 ). One such natural product, R. turkestanicum , belongs to the Polygonaceae family and is composed of active ingredients with various pharmacological and biochemical properties ( Ghorbani et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, stabilizing the mitochondria can prevent doxorubicin-induced cardiotoxicity ( Montaigne et al, 2010 ). Indeed, recent studies have reported that natural products may be appropriate alternatives for chemical agents in various diseases ( Momtazi et al, 2017 ; Bagherniya et al, 2018 ; Alidadi et al, 2020 ; Soltani et al, 2021 ). One such natural product, R. turkestanicum , belongs to the Polygonaceae family and is composed of active ingredients with various pharmacological and biochemical properties ( Ghorbani et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The andrographolide effect in stimulating the immune system in the body, and especially phagocytic activity that stimulates the production and flow of bile, protects the hepar from toxins, against the damage effects caused by free radicals. Andrographolide also showed protective activity in the fight against chemical-induced toxicity (Polash et al 2017;Soltani et al 2021;Rachmani E. 2019). APL serves as an appetite enhancer, but high doses of APL can result in nausea vomiting, bad stomach and loss of appetite (Mustafa et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Improving cellular cholesterol efflux by targeting macrophages is one approach. LXR agonism is one of the mechanisms that increases macrophage efflux capability [21].…”
Section: Enhancing the Ability To Excrete Cholesterolmentioning
confidence: 99%